Enzymatic basis for hydrolytic versus phosphorolytic mRNA degradation in Escherichia coli and Bacillus subtilis. - Deutscher, M P (1991)
The rapid synthesis and breakdown of mRNA in prokaryotes can impose a significant energy drain on these cells. Previous in vivo studies [Duffy, J. J., Chaney, S. G. & Boyer, P. D. (1972) J. Mol. Biol. 64, 565-579; Chaney, S. G. & Boyer, P. D. (1972) J. Mol. Biol. 64, 581-591] indicated that while RNA turnover in Escherichia coli was hydrolytic, it was nonhydrolytic in Bacillus subtilis. Here we provide an explanation for these observations based on enzymatic analysis of extracts of these two organisms. RNA degradation to the mononucleotide level in E. coli extracts is due solely to two active ribonucleases, RNase II and polynucleotide phosphorylase, which act hydrolytically and phosphorolytically, respectively. RNase II activity represents close to 90% of the total activity of the extract, as expected for predominantly hydrolytic degradation in this organism. In contrast, RNase II is absent from B. subtilis extracts, and the primary mode of RNA degradation is phosphorolytic, employing the Bacillus equivalent of polynucleotide phosphorylase and releases nucleoside diphosphates as products. A low level of a Mn2(+)-stimulated, hydrolytic ribonuclease is also detectable in B. subtilis extracts. Overall, E. coli and B. subtilis extracts differ by about 20- to 100-fold, depending on the substrate, in their relative use of hydrolytic and phosphorolytic routes of RNA degradation. The relation of the mode of mRNA degradation to the environment of the cell is discussed.